(3GdeNJGQGJ ddaJhis - (3Ydj Hf CMeO Hf eMeO GdLeGdj GdHcQj , YdGA GdOjf,J (B932 (3g` s
(3ChdgG (B:s
(3Gddge HMeOc GdHOGjI hHYO aEf CabQ YHGO Gddg Edi QMeJg Ydi Hf CMeO GdLeGdi bGd (B: (3deG habfi Gddg HdWag dHjGf CMcGeg dYHGOg HGdEaJGA YeG jSJaJhfg ef GdhGbYGJ aCdaJ eNJUQkG egPHkG eMQQkG hSejJg s
(3BNQgG (B:s
(3HNdGa dhTgO GdBNQ ddChd HhUjI KdK eGdg , hHNdGa eGdh TgO CMOgeG ddBNQ HhUjI KdK eGdg hTgO GdBNQ ddChd eKd Pdc MjK dGjLhR Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B64 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B25 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B742s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1624s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs